Enhancing Osseointegration of TC4 Alloy by Surficial Activation Through Biomineralization Method - Zhou, Liang; Pan, Meng; Zhang, Zhenghua; Diao, Zijie; Peng, Xiaochun (Frontiers in Bioengineering and Biotechnology, 2021)
Titanium (Ti) alloys have been applied to biomedical implants for a long time. Although Ti alloys are biocompatible, efforts have been continuously made to improve their bone conductivity and osteogenesis for enhancing their performance. Silk fibroin (SF) is a natural biomaterial with excellent biomedical and mechanical properties, and hydroxyapatite (HAP) nanocomposites derived from SF are promising for producing “artificial bone” owing to their biomedical applicability and strong mechanical functions. Therefore, we built an SF coating on the surface of Ti-6Al-4V alloy, and then the incubated SF-coated Ti alloy were immersed in simulated body fluid to induce mineral deposition of HAP on the alloys. The results from Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) analysis, and Attenuated Total Reflection–Fourier Transform Infrared Spectroscopy (ATR-FTIR) confirmed the deposition of a mineral layer on the SF film surface. The proliferation, adhesion, and differentiation of MG-63 were tested, along with the BMP-2, COX-2, and OPG expression and protein content in the MG-63. Both Ti+SF and Ti+SF+HAP groups exhibited significantly better performance than a control Ti group with regard to the cell adhesion, cell proliferation, and protein expression. Furthermore, the hybrid layer comprising HAP and SF delivered more significant improvement of the osseointegration than the SF alone. It is hoped that the proposed methods can be used for constructing modified surfaces on Ti alloys, as they endowed the implants with good osteogenic potential.